RISK FACTORS ASSOCIATED WITH FEMALE SEXUAL DYSFUNCTION IN MARRIED WOMEN WORKING IN HEALTH CARE SYSTEM - Ridwan, Fanny Riana; Ali, Zulfikar; Gautami Hidayah, Kemala; Faradila Utari, Nazlah; Innayah, Ulfa (Indonesian Urological Association, 2023)
ABSTRACT Objective: In this study, we want to evaluate the risk factors associated with sexual dysfunction in married women working in health care system. Material & Methods: The sexual function was assessed in the questionnaire using Female Sexual Function Index (FSFI). The analysis was conducted using chi-square test or Fisher Exact Test. Results: All participants who were overweight/obese had highest pain problem (p-value 0.034). Women with diabetes mellitus had higher satisfaction problems (p=0.002, OR 13.13, CI 1.73-99.91). The females who used contraception had significantly lower orgasm problems (p<0.004, OR 0.33, CI 0.15-0.72. Participants who worked as medical staff such as nurse/midwife, pharmacist, radiographer had higher pain problems (71.43%) compared to medical staff (administration staff) (OR 27.47, CI 3.73-202). Conclusion: The BMI (overweight/obesity), diabetes mellitus, the use of contraception, and the medical occupation were the significant risk factors to sexual dysfunction problem in women working in the hospital. Keywords: Female sexual dysfunction, working women, hospital.